2021
DOI: 10.1111/1742-6723.13836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mobile mindfulness on emergency department work stress: A randomised controlled trial

Abstract: Objective: High-occupational stress among ED staff has a detrimental impact on both staff wellness and patient care. The objective of the study is to determine whether 4 weeks of smartphone app-guided mindfulness practice reduces stress levels of ED staff. Methods: This two-arm randomised controlled trial was conducted in two Australian EDs in 2019-2020. Eligible participants were randomly assigned (1:1) to either an App group or a Wait to Treat group to practice daily 10 min app-guided mindfulness for 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…The results from the few available RCTs on digitally supported mindfulness interventions among nurses working in acute inpatient care settings are heterogeneous, do not include long-term follow-up (maximum 4 months), and have rarely been conducted in Europe (except for the study by Fiol-DeRoque et al [ 16 ]) [ 20 - 23 ]. Two studies showed significant reductions in anxiety and stress, as well as an increase in work satisfaction, following participation in digitally supported mindfulness interventions after 3 months [ 20 - 22 ]. However, 3 studies found no significant between-group differences in their outcomes [ 16 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results from the few available RCTs on digitally supported mindfulness interventions among nurses working in acute inpatient care settings are heterogeneous, do not include long-term follow-up (maximum 4 months), and have rarely been conducted in Europe (except for the study by Fiol-DeRoque et al [ 16 ]) [ 20 - 23 ]. Two studies showed significant reductions in anxiety and stress, as well as an increase in work satisfaction, following participation in digitally supported mindfulness interventions after 3 months [ 20 - 22 ]. However, 3 studies found no significant between-group differences in their outcomes [ 16 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies showed significant reductions in anxiety and stress, as well as an increase in work satisfaction, following participation in digitally supported mindfulness interventions after 3 months [ 20 - 22 ]. However, 3 studies found no significant between-group differences in their outcomes [ 16 , 22 , 23 ]. They had an observation time of 1 month and 1 to 4 months [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of these apps are the Calm app [ 43 , 57 ] and Headspace. Effectiveness in terms of, e.g., stress perception, perceived mindfulness and perceived well-being could be demonstrated [ 27 , 34 , 39 , 40 ]. Deady et al (2020) found that the HeadGear app decreased depressive symptoms, anxiety symptoms and sick days, though it increased self-rated work productivity and demonstrated high acceptability and utility.…”
Section: Resultsmentioning
confidence: 99%